Hukum Waris Islam Dipandang Dari Perspektif Hukum Berkeadilan Gender - Maryati Bachtiar (Fakultas Hukum Universitas Riau, 2012)
As state which its resident majority believe in Islam enabled by a lot of society member using Islam punish system. But along with the times marked by technological advances and the principles of Islamic law continues to progress rapidly and always follow the changing times in order to benefit people in the world. Without differentiating woman and men. from breakdown of the solution can pulled a conclusion that hereditary law of Islam have accomodated law principle which with justice gender.